(untitled) (Brazilian Geographical Journal, 2023)
The implementation of a database, logically and coherently related, provides a better organization, analysis, correlation, availability, accessibility, and security to georeferenced data. In this sense, a proposal is presented a geotechnical and geoenvironmental database to support research related to modeling sediment generation in erosion and deposition in hydroelectric power plant (HPP) reservoirs, at various scales. Supported by a literature review, the work presents an expository, descriptive, and applied approach. The results demonstrate the structuring of the database, from the requirements definition, the conceptual modeling and physical implementation, the development of metadata and data dictionary, and maintenance tools and other functionalities. The proposal demonstrates benefits, especially by: 1) making it possible to handle a large amount of data; 2) minimizing data loss and redundancy; 3) ensuring data availability and remote access.